E-Commerce Implementation Training Provides Business Opportunities for the Young Generation in Medan Johor District - Juniarti, Juniarti; Ferine, Kiki Farida; Batubara, Soulthan Saladin (International Conference on Sciences Development and Technology, 2023)
Following the COVID-19 outbreak, using technology to run a business has become essential for all business actors. increased economic expansion along with the arrival of the